Effective use of a Limited Antiviral Stockpile for Pandemic Influenza - Arinaminpathy, N; Savulescu, J; Mclean, A (2009)
Just allocation of resources for control of infectious diseases can be profoundly influenced by the dynamics of those diseases. In this paper we discuss the use of antiviral drugs for treatment of pandemic influenza. While the primary effect of such drugs is to alleviate and shorten the duration of symptoms for treated individuals, they can have a secondary effect of reducing transmission in the community. However, existing stockpiles may be insufficient for all clinical cases. Here we use simple mathematical models to present scenarios where the optimum policies to minimise morbidity and mortality, with a limited drug stockpile, are not always the most intuitively obvious and may conflict with theories of justice. We discuss ethical implications of these findings. © Springer Science + Business Media B.V. 2009.